Socio-environmental impacts of tourism in Malaysia: Seeking sustainable alternatives - Karim, A.H.M Zehadul (Institute for Research and Journals ( IRAJ ), 2018)
Tourism in Malaysia has been identified as one of the largest service oriented industries, adding a substantial amount of yearly into its GDP which provides economic benefits to millions of people in the commercial and small-scale business sectors of the country.Based on such enormous propensity, it can be said that tourism is an excellent source of income as it creates job opportunities for a huge number of local people and allows them to be economically pursuant and self-sufficient. Geographically, Malaysia has a wonderful natural beauty and at the same time, it practices more or less a tolerant and accepting cultural attitude for which tourists from different parts of the world are attracted. Nonetheless, tourism produces negative impacts particularly on local values where people are often suspected of being assimilated into unfamiliar behaviours brought in by the outsiders. While tourism enhances urban expansion and settlement, it may also damage the natural eco-system as it is converted into pavements and dormitories, creating debates on the issue. Based on such paradoxical debates, this paper is designed to consider firstly, both positive and negative impacts of tourism in Malaysia and finally suggest a rhetorically yet acceptable solution based on its scope in the country.